Zooarchaeology of the Roman-Saxon transition - Sheeran, Lucy (2016)
The period between the Roman withdrawal from Britain and the beginning of the Anglo-Saxon period is a time of social, cultural, and political change. It was once referred to as the ‘dark ages’ due to the limited understanding we have of this period.